Cabeço, o povoado submerso : a proteção jurídica ao patrimônio cultural subaquático brasileiro nas lições da arqueologia no Velho Chico - Rodrigues, Maria Clara Alécio (2023)
The Underwater Cultural Heritage (UCH), a kind of heritage found submerged by salty or sweet bodies of water, can be understood as a time capsule capable of holding the memory of a civilization or social group. His location, out of the reach of the eyes, ends up putting him in a position of greatest risk of aggression or destruction, ends up putting him in a position of greater risk of aggression or destruction, than that faced by the earth's cultural heritage, requiring an even greater effort of protection from the right. Thus, the research focused on international and national standards of protection, more punctually the Annex to the UNESCO Convention for the Protection of Underwater Cultural Heritage of 2001, the Brazilian Constitution and Law nº 7.542/86 (law on the research, exploitation, removal and demolition of sunken things or property), in order to highlight the gaps in the regulations in relation to the UCH. Moved by the monitoring of the archaeological research project of the Lower São Francisco River, this research sought to investigate the instruments of that archaeological experience in the search to fill the fluidity of Brazilian normative international level in relation to the object to be protected. And faced the following problem: What instruments of archaeological research (accompanied in the project of The Lower San Francisco) can be useful in closing the gaps left by national and international legislation as regards the legal protection of underwater heritage? The hypothesis of conclusion was that the protection of the UCH could be strengthened with the prior adoption of the instruments of protection revealed by the accompanied project, namely: in situ preservation, the national archaeological charter, musealization and heritage education. Thus, it is proposed, as preventive action, for the regulation of each specific regime, for use of archaeological research in the legal protection of the UCH, as an essential step for the adoption of legal measures capable of preventing or minimizing illegal actions such as trafficking and harmful commercial exploitation of submerged property in order to prevent their irreversible dispersion, plunder or destruction.